Evaluation of 105 Cases of Dyspepsia by Upper Gastrointestinal Endoscopy and Ultrasonography of Hepatobiliary System in a Rural Setting (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Dyspepsia affects up to 40% of the general population and significantly reduces the quality of life. Dyspeptic symptoms may be associated with endoscopically negative conditions, such as functional dyspepsia, or with organic lesions like peptic ulcer and oesophagitis which are easily detected by endoscopy. On the other hand, such lesions may also be asymptomatic and there is not always a clear cause and effect relationship between endoscopic findings and symptoms.Objective: To determine the prevalence of significant endoscopic lesion and or ultrasonographic findings and their association with dyspeptic symptoms in Bangladeshi rural population.Materials and Methods: This prospective cross sectional study was carried out in Nov 2015 to Dec 2015 in a field mobile hospital of Bangladesh Army, established in Daudkandi, Comilla where total 1094 uninvestigated dyspeptic patients were invited to participate in this cross sectional study and 105 typical dyspeptic patients were finally recruited as per Rome III criteria. Participants underwent clinical assessment through a preformed structured questionnaire and non video upper gastrointestinal endoscopy (UGIE) and ultrasonogram (USG) of hepatobiliary system (HBS).Results: The mean age of 105 participants (male-29; female-76) studied was 36.51±7.26 years with female preponderance (72.38%). Predominant symptoms were epigastric pain (69.52%), flatulence (34.28%), heart burn (28.57%) and diffuse abdominal pain (22.85%). Regarding treatment 48(45.71%) patients took proton pump inhibitors (PPI), 24 patients (22.85%) took H2 receptor blocker and 13 patients (12.38%) were on antacids irregularly. Seventeen patients (16.15%) had no history of medications for dyspepsia. Most of the patients (76.19%) had symptoms of less than 5 years. Organic dyspepsia was found in 68(64.76%) and functional dyspepsia in 37(35.23%) participants. Percentage of functional dyspepsia in male was 24.13% and in female it was 39.47% and the difference was statistically significant (p